2015
DOI: 10.1093/rheumatology/kev200
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of systemic disease in primary Sjögren's syndrome: EULAR-SS Task Force recommendations for articular, cutaneous, pulmonary and renal involvements

Abstract: The proposals included in this article are a first step to developing an optimal diagnostic approach to systemic involvement in primary SS and may pave the way for further development of evidence-based diagnostic and therapeutic guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
233
0
16

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 253 publications
(263 citation statements)
references
References 26 publications
14
233
0
16
Order By: Relevance
“…However, nonspecific interstitial pneumonitis (NSIP) seems to be the most common pathological subtype revealed by lung biopsy [36,46,51,[87][88][89]. However, these studies are based on small samples.…”
Section: Ild In Sjögren's Syndromementioning
confidence: 99%
See 4 more Smart Citations
“…However, nonspecific interstitial pneumonitis (NSIP) seems to be the most common pathological subtype revealed by lung biopsy [36,46,51,[87][88][89]. However, these studies are based on small samples.…”
Section: Ild In Sjögren's Syndromementioning
confidence: 99%
“…However, these studies are based on small samples. A recent review of 146 histological cases in the literature found 45% NSIP, 16% usual interstitial pneumonitis (UIP), 7% organising pneumonia, 15% LIP and 17% other pathologies [89]. The main symptoms of these ILDs are dyspnoea and cough.…”
Section: Ild In Sjögren's Syndromementioning
confidence: 99%
See 3 more Smart Citations